2017
DOI: 10.1111/jop.12579
|View full text |Cite
|
Sign up to set email alerts
|

Patients with high c‐MYC‐expressing squamous cell carcinomas of the tongue show better survival than those with low‐ and medium‐expressing tumours

Abstract: The present findings show that expression of c-MYC has prognostic value in squamous cell carcinoma of the tongue, and could be useful in choice of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Cyclin D1 is a cell cycle-related factor associated with G1/S stage transition. C-Myc encodes phosphorylated proteins, which facilitate cell proliferation and differentiation (28). Cyclin D1 and c-Myc are downstream target genes of the Wnt/β-catenin signaling pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 is a cell cycle-related factor associated with G1/S stage transition. C-Myc encodes phosphorylated proteins, which facilitate cell proliferation and differentiation (28). Cyclin D1 and c-Myc are downstream target genes of the Wnt/β-catenin signaling pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, compared with older patients, young patients have no history of tobacco or alcohol abuse. Furthermore, the time of exposure to these well‐known risk factors may not have been sufficient to promote malignant transformation, suggesting the involvement of other external or internal factors in the development of tongue cancer in this population 17‐21 . In the past years, an increasing incidence of TSCC has been registered in those countries where the primary prevention campaign to stop smoking and drinking has been active, thus suggesting the possible emerging role of new etiological or genetic factors driving carcinogenesis 5,10,11,22‐24 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies displayed significant association between the overexpression of c-Myc and poor prognosis in numerous tumors, while other studies revealed an opposite correlation. On the contrary, some reports did not support either of these conclusions (Zaharieva et al, 2005;Tsiatis et al, 2009;Massari et al, 2015;Zeng et al, 2015;Strindlund et al, 2017;He et al, 2018).…”
Section: Discussionmentioning
confidence: 95%